2013
DOI: 10.1111/jfd.12148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vitro exposure to mercury on male gonads and sperm structure of the tropical fish tuvira Gymnotus carapo (L.)

Abstract: This study investigated the progressive effects of HgCl2 in the testis and sperm of the tropical fish tuvira Gymnotus carapo L. exposed to increasing Hg concentrations (5-30 μm) and increasing exposure times (24-96 h). Histopathology and metal concentrations in the testis were observed. Hg concentrations in the testis reached 5.1 and 5.2 μg g(-1) in fish exposed to 20 and 30 μm of Hg, respectively. Hg effects on testicular tissue were observed even at low Hg concentrations, with no alterations in gonadosomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We used gonads at the mature stage, on mussels obtained in January and vacuolized areas were observed only in mussels exposed to HgCl 2 and not in control condition. The observed morphological changes of seminiferous follicles, as vacuolization and decrease of germ cell compartment thickness, were reported also in fish [ 52 ] and in mammal testis [ 53 , 54 ] after HgCl 2 treatment. A growing number of studies show that sex steroids are widespread in molluscs [ 55 ].…”
Section: Discussionsupporting
confidence: 53%
“…We used gonads at the mature stage, on mussels obtained in January and vacuolized areas were observed only in mussels exposed to HgCl 2 and not in control condition. The observed morphological changes of seminiferous follicles, as vacuolization and decrease of germ cell compartment thickness, were reported also in fish [ 52 ] and in mammal testis [ 53 , 54 ] after HgCl 2 treatment. A growing number of studies show that sex steroids are widespread in molluscs [ 55 ].…”
Section: Discussionsupporting
confidence: 53%
“…The toxicity of mercury has been evaluated at high doses (micromolar), in some organisms, such as the European clam (Ruditapes decussatus), in which Hg significantly reduced sperm viability [18] and also in Ciona intestinalis on which mercury affected early developmental stages. In addition, this metal impaired the testes function of the tropical fish Gymnotus carapo (L.), producing a decrease in sperm count and the alteration in sperm morphology [19]. Moreover, an in vivo study performed by Lahnsteiner et al (2004) [20] showed that mercury had significantly decreased the percentage of sperm motility and velocity of Clarias gariepinus and Lota lota [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several animal studies indicate that mercury is a male reproductive toxicant, but human studies are few and contradictory. Vergilio et al [95] investigated the toxic effects of mercury chloride (1 μM -30 μM) on testes and sperms of tropical fish (Gymnotuscarapo) and showed decrease in the sperm count (36.8%) after 20 μM/24 h treatment and subsequent decrease (48.7%) was observed after 20 μM/96 h. Hg (20 μM) also altered the sperm morphology in 24 h and 96 h where sperm head abnormalities were present.…”
Section: Effect Of Mercuric Chloride On Tyrosine Phosphorylationmentioning
confidence: 99%